Sustentabilidade ambiental em empresas de base tecnológica de São Carlos: estratégias ambientais - Gomes, Cintia (2011)
Technology-based firms (TBF s) are expected to fit market demands more easily for being technologically dynamic, more flexible due to their size and their intense knowledge grounds. This research investigated how TBF s of São Carlos/SP have involved in environmental sustainability. It focuses on environmentally friendly strategies employed by companies in sectors that are likely to be environmentally impactful. The survey verifies the environmental performance of firms by identifying if companies have done effective actions, and investigates whether they have proactive, preventive or reactive attitudes in response to pressure from legislation, environmental certification or public pressure. This research characterized those companies considering, among other factors, their relationship with local universities and research centers, characterized the entrepreneurs and verified if environmental certification is usual with the TBF s. This research is supported by work previously done on TBF s and manuals and norms, among other sources. Data were collected by means of questionnaire sent to 10 companies from industrial sectors whose production processes potentially impact the environment. It was possible to draw a partial picture of the environmentally friendly strategies employed, verify the low certification of ISO 14001 and the need for incorporating more effective environmentally friendly practices by those companies. Entrepreneurs of the companies investigated have a high educational level, and the employees have an educational level higher than those usually observed in traditional types of businesses. Most of the founders of the companies investigated come from educational and research institutions of São Carlos which also influence the technological areas developed by the companies.